The impact of the FRTB on Market Risk Capital for the South African InterBank Interest Rate Market - Mwanza, Jacob (African Institute of Financial Markets and Risk Management, 2021)
Regulations require banks to hold a minimum amount of capital for market risk resulting from their trading operations and prescribe two approaches to calculating this minimum capital requirement: (i) a Standardised Approach (SA); and (ii) an Internal Models Approach (IMA). The global financial crisis of 2008 highlighted flaws in the Basel 2 regulatory framework used by banks to calculate market risk capital charges for trading operations. In 2009, Basel 2.5 was introduced to deal with some but not all of the flaws of Basel 2. Both Basel 2 and 2.5 use the Value at Risk (VaR) risk measure as the basis to determine IMA capital charges. From 2022 onwards, Basel 2.5 will be replaced by the Fundamental Review of the Trading Book (FRTB), a new framework for calculating market risk capital charges for trading operations. The FRTB replaces VaR with the Expected Shortfall (ES) risk measure in the IMA and introduces a new SA. This dissertation investigates the impact the FRTB will have on market risk capital charges for portfolios of linear South African interbank interest rate products. Capital charges are calculated for these portfolios under the Basel 2, Basel 2.5 and FRTB regulatory frameworks. A comparison and analysis of the resulting capital charges is then presented.